The Extent of Applying the Balanced Scorecard at the Jordanian Universities: Comparative study between the Government and Private Universities - siam, walid zakaria; Al-Masri, Rami Najeh (Archives of Business Research, 2017)
This study aims to identify the application extent of Balanced Scorecard (BSC) in Jordanian universities, and the variation extent in application between government and private Universities. It also aims to identify the obstacles (limitations) that limit the application of (BSC) in Jordanian Universities, and indicate whether these constraints (limitations) vary between government and private Universities. To achieve objectives of the study, the researchers prepared a questionnaire which was distributed in Jordanian government and private universities, total of (28) Universities (10 government universities and 18 private universities) (according to Jordanian Ministry of Higher Education and Scientific research Statistics of 2017). Questionnaires were distributed to financial managers, internal auditing managers, quality control and assurance managers, heads of accounting departments and employees working in finance departments of these universities. The study concluded many results. Important ones can be summarized as follows: The Jordanian universities apply the Balanced Scorecard (BSC) in a moderate degree. There is variation in the implementation degree of the Balanced Scorecard (BSC), in favor of the Jordanian private universities. There are constraints (limitations) limit the application of the Balanced Scorecard (BSC) in Jordanian universities (government and private) in a moderate degree. There is a slight variation in the existence degree of constraints (limitations) that limit the application of the Balanced Scorecard (BSC) between government and private universities in favor of the private universities. In the light of this study results, the researchers presented a set of recommendations including: importance of providing appropriate environment for application of the Balanced Scorecard (BSC) in the government Jordanian universities and more attention in applying to reach a high degree similar to the private Jordanian universities. Joint efforts must be combined between the Jordanian government and private universities to curb constraints (limitations) in the application of the Balanced Scorecard (BSC) efficiently.